Lights, camera…research! Short film and social media to recruit to HIV research in Indonesia. (May 2022) - Gedela, K; Luis, H; Loverian, RF; Maharani, S; Rajus, N; Wignall, FS; Garner, A; Sukmaningrum, E; McOwan, A; Nwokolo, N; Whitlock, G; Irwanto, I
Introduction: HIV prevalence among men who have sex with men has increased in Indonesia, amid reports of growing stigma against lesbian, gay, bisexual and transgender individuals and policies that have pushed back public health outreach to these groups. Methods: We assessed the utility of tailored short film and targeted social media engagement to recruit men who have sex with men in Indonesia to HIV social science research. A short HIV testing promotion film, anonymised short survey and invite to a wider research study was embedded on a website platform and disseminated using geo and social/community group targeting for 1 month via a social networking app and social media platforms. Results: From 3 January 2021 to 3 February 2021, there were over 2200 hits of the website within Indonesia. A total of 177 male web users who identified as men who have sex with men or preferred not to declare their sexuality, engaged by watching the short film and completing the survey, they were aged between 17 and 60 years old, of Indonesian nationality and living in Indonesia. Of these, 88% indicated having at least one HIV test in their lifetime, 66% had felt shame with respect to their sexuality and 53% indicated feeling afraid to have a HIV test. Ninety (51%) of the 177 validated using their email or mobile phone number demonstrating willingness to be contacted to join a further study. Twenty-three eligible men who have sex with men, aged 21–55 years old, joined a further social science research study. Participants were from diverse backgrounds and included men born in provinces outside Bali, of different socio-economic and employment backgrounds and diverse relationship contexts. Discussion: Engaging, empowering digital media involving key health messaging can provide health education in more effective ways, build trust and bring communities together. Targeted digital and social media approaches could reach increasingly marginalised and vulnerable communities to promote individual and public health and enable recruitment to valuable medical research.